Digital Transformation in Human Resource Management: A Systematic Literature Review - Indra Bratamanggala, Rieki (Siber International Journal of Education Technology (SIJET), 2023)
Digital transformation has become a key factor in changing the way organizations manage human resources (HR). This study aims to identify the challenges and opportunities arising from the adoption of digital technology in HR management through a literature review. Based on the analysis of various previous studies, some of the main challenges faced by organizations include technological competency gaps, complex system integration, concerns about data privacy and security, and resistance to change from employees and management. On the other hand, digital transformation offers significant opportunities such as increased operational efficiency, utilization of data for better decision-making, employee skill development, and enhanced employee engagement. The findings of this study indicate that to successfully implement digital transformation in HR management, organizations need to develop comprehensive and integrated strategies. Recommended steps include investing in technology training for employees, careful planning of system integration, implementing strict data security policies, and developing effective communication and change management programs. By addressing the challenges and leveraging the opportunities, organizations can enhance HR performance and achieve competitive advantage in the digital era.